The interplay between the tumor microenvironment and tumor-derived small extracellular vesicles in cancer development and therapeutic response - Xuanyu Guo; Jiajun Song; Miao Liu; Xinyi Ou; Yongcan Guo (Cancer Biology & Therapy)
The tumor microenvironment (TME) plays an essential role in tumor cell survival by profoundly influencing their proliferation, metastasis, immune evasion, and resistance to treatment. Extracellular vesicles (EVs) are small particles released by all cell types and often reflect the state of their parental cells and modulate other cells’ functions through the various cargo they transport. Tumor-derived small EVs (TDSEVs) can transport specific proteins, nucleic acids and lipids tailored to propagate tumor signals and establish a favorable TME. Thus, the TME’s biological characteristics can affect TDSEV heterogeneity, and this interplay can amplify tumor growth, dissemination, and resistance to therapy. This review discusses the interplay between TME and TDSEVs based on their biological characteristics and summarizes strategies for targeting cancer cells. Additionally, it reviews the current issues and challenges in this field to offer fresh insights into comprehending tumor development mechanisms and exploring innovative clinical applications.